Prospects of compounds of herbal plants as anticancer agents: a comprehensive review from molecular pathways - Situmorang, Putri Cahaya; Ilyas, Syafruddin; Nugraha, Sony Eka; Syahputra, Rony Abdi; Nik Abd Rahman, Nik Mohd Afizan (Frontiers in Pharmacology, 2024)
Cancer refers to the proliferation and multiplication of aberrant cells inside the human body, characterized by their capacity to proliferate and infiltrate various anatomical regions. Numerous biochemical pathways and signaling molecules have an impact on the cancer auto biogenesis process. The regulation of crucial cellular processes necessary for cell survival and proliferation, which are triggered by phytochemicals, is significantly influenced by signaling pathways. These pathways or components are regulated by phytochemicals. Medical plants have shown to be a significant reservoir of diverse anticancer medications employed within the realm of chemotherapy. The anticancer effects of phytochemicals are mediated by several methods, including the induction of apoptosis, cessation of the cell cycle, inhibition of kinases, and prevention of carcinogenic substances. This paper provides an analysis of the phytochemistry of seven prominent plant constituents, namely alkaloids, tannins, flavonoids, phenols, steroids, terpenoids, and saponins. The investigation focuses on the involvement of the MAPK/ERK pathway, TNF signaling, death receptors, p53, p38, and actin dynamics. Hence, this review has examined a range of phytochemicals, encompassing their structural characteristics, and potential anticancer mechanisms. It has underscored the significance of bioactive compounds produced from plants in the prevention of cancer, utilizing diverse molecular pathways. In addition, this endeavor also seeks to incentivize scientists to carry out clinical trials on anticancer medications derived from plants.Cancer encompasses a wide range of illnesses characterized by the abnormal growth and multiplication of abnormal cells within the human body. These abnormal cells exhibit the ability to proliferate and invade any region of the organism (Brown et al., 2023). Cancer is considered the second leading cause